Non-Selective Inhibition of Transformed Cell Growth by a Protease Inhibitor - Chou, Iih-Nan (1974)
The protease inhibitors N-tosyl-L-phenylalanylchloromethyl ketone (TPCK) and N-tosyl-L-lysylchloromethyl ketone (TLCK) have previously been shown to selectively inhibit growth of simian virus 40-transformed cells, suggesting that proteolytic enzymes play a role in loss of cellular growth control following viral transformation. In contrast, this study shows that TPCK-mediated growth inhibition is non-selective, since the growth of both simian virus 40-transformed and untransformed 3T3 cells is similarly reduced by TPCK treatment. Under certain conditions, TPCK treatment of simian virus 40-transformed cells yields a reversible “growth plateau” condition which mimics, but is not equivalent to, contact inhibition of growth. The growth inhibitory effects of TPCK are due to inhibition of protein synthesis, since TPCK treatment resulted in a diminution of protein synthesis and since the “growth plateau” effect was also observed in cultures treated with cycloheximide.